2010
DOI: 10.1016/j.molcel.2010.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositides Are Essential Coactivators for p21-Activated Kinase 1

Abstract: SUMMARY Phospholipid-enriched membranes such as the plasma membrane can serve as direct regulators of kinase signaling. Pak1 is involved in growth factor signaling at the plasma membrane and its dysregulation is implicated in cancer. Pak1 adopts an autoinhibited conformation that is relieved upon binding to membrane-bound Rho GTPases Rac1 or Cdc42, but whether lipids also regulate Pak1 in vivo is unknown. We show here that phosphoinositides, particularly PIP2, potentiate Rho-GTPase-mediated Pak1 activity. A po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 29 publications
3
50
0
Order By: Relevance
“…Given that PAK6 targets to cell-cell adhesions independent of catalytic activity, and that PAK6 readily accumulates at cell-cell adhesions before their disassembly, the latter possibility seems more likely. Indeed, as noted earlier, the polybasic membrane-targeting site of PAK1 has been reported to contribute to PAK1 activation (Strochlic et al, 2010) and the same might be true for type II PAKs. Additional studies will be required to identify potential membrane-associated local activators of type II PAKs, an area already of growing interest given their unique activation mechanisms (Baskaran et al, 2012;Ha et al, 2012).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Given that PAK6 targets to cell-cell adhesions independent of catalytic activity, and that PAK6 readily accumulates at cell-cell adhesions before their disassembly, the latter possibility seems more likely. Indeed, as noted earlier, the polybasic membrane-targeting site of PAK1 has been reported to contribute to PAK1 activation (Strochlic et al, 2010) and the same might be true for type II PAKs. Additional studies will be required to identify potential membrane-associated local activators of type II PAKs, an area already of growing interest given their unique activation mechanisms (Baskaran et al, 2012;Ha et al, 2012).…”
Section: Discussionsupporting
confidence: 60%
“…Although a few basic residues are present N-terminal to the CRIB motif in PAK1, they are interrupted by positively charged glutamic acid residues, which might be enough to interrupt any cell-cell targeting functionality. PAK1 does contain a polybasic stretch further upstream, which has been reported to function as a nuclear localization signal (Singh et al, 2005) and to interact with membrane lipids to contribute to PAK1 activation and membrane recruitment (Strochlic et al, 2010), but the presence of this sequence, at least in the context of GFP-tagged PAK1, does not appear to be sufficient for specific cell-cell adhesion targeting. It also remains a possibility that differences in the Cdc42-binding region of the PAK isoforms might contribute to differential targeting, even among type II isoforms, although the CRIB motif and many of the residues C-terminal to the motif shown to be important for Cdc42 binding are well-conserved (PDB: 2ODB) (Thompson et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The liposome-binding assays were performed essentially as previously described 61 . Briefly, liposomes containing PC:PE (50:50) or PC:PE:PtdInsP(n) (45:45:10) were prepared by mixing chloroform stocks, drying and resuspending using a bath sonicator in 10 mM HEPES (pH 7.7), 100 mM NaCl, 200 mM sucrose and 5 mM EGTA.…”
Section: Methodsmentioning
confidence: 99%
“…9,37 Recently, it was reported that PIP 2 along with rac1 or cdc42 is necessary for activation of PAK1 by blocking the autoinhibitory domain of PAK1 both in vitro and in vivo. 41 Thus, Wnt3a-mediated PIP 2 production might not only be necessary for phosphorylation and aggregation of LRP6 but also for activation of PAK to phosphorylate Merlin. To determine the role of PIP 2 in Wntmediated Merlin phosphorylation, HEK293T cells were treated with neomycin, a PIP 2 scavenger, 42,43 with or without Wnt3a-CM.…”
Section: Wnt3a-mediated Phosphorylation Of Lrp6 Is Inhibited Bymentioning
confidence: 99%